A New Supermicrosurgery Training Model of Saphenous Artery and Great Saphenous Vein Anastomosis for Development of Advanced Microsurgical Skills - Bas, Can Emre; Cwykiel, Joanna; Siemionow, Maria (Journal of Reconstructive Microsurgery, 2017)
Background This study aimed to confirm the feasibility and reliability of saphenous artery (SA) and great saphenous vein (GSV) anastomosis as a new supermicrosurgery training model and to compare the one-way-up anastomosis with the currently used end-to-end anastomosis technique.Methods Twenty supermicrosurgical anastomoses were performed in 10 Sprague Dawley rats. The external diameters of SA and GSV were measured using Leica LAS EZ software. The right-side SA and GSV anastomoses were performed using the standard end-to-end anastomosis technique. The left-side SA and GSV anastomoses were performed using the one-way-up technique with 11–0 monofilament-interrupted sutures. The duration of the surgery, patency rates, and technical challenges of the two anastomoses methods were compared.Results The mean external diameters of SA and GSV were 0.273 ± 0.03 and 0.291 ± 0.02 mm, respectively, which qualify these vessels for supermicrosurgical training. The vessels were easily accessible and both anastomosis techniques were feasible. The one-way-up technique was proven to be faster as compared with the end-to-end anastomosis technique (artery: 34 ± 2.55 vs. 40.4 ± 2.97 minutes, p = 0.02; and vein: 37 ± 4.85 vs. 44 ± 2.35 minutes, p = 0.05, respectively). Short-term patency rates for arteries and veins were 100% for both techniques. Seven-day anastomosis patency rates for arteries and veins were 80 and 100% for the end-to-end technique and 100 and 80% for the one-way-up technique, respectively.Conclusions We confirmed that saphenous pedicle is suitable for creating a supermicrosurgery training model for practicing the ultrafine motor skills. To the best of our knowledge, this is the first report on supermicrosurgery of SA and GSV in the rat model.
Keywords: one-way-up anastomosis technique; supermicrosurgery training model; saphenous artery and great saphenous vein